Regional green belts in the Ruhr region. A planning concept revisited in view of ecosystem services - Zepp, Harald (ERDKUNDE, 2018)
The idea of regional green belts in the Ruhr region (Germany) dates back to 1912, but only 60 years ago, the term regional green belt appeared in official German spatial planning, and ever since, regional green belts as a theoretical concept and a planning category form an integral part of regional planning in the area. This paper tracks back the changing concepts, functions of the regional green belts, it analyzes their present state and proposed future. From the starting point of their formal existence in the Regional Development Plan as of 1966, the original regional green belts (RGBs) significantly lost open space and consequently areas providing ecosystem services diminished. Parts of RGBs were transformed into settlement and areas for traffic and technical infrastructure, whereby the loss is spatially unevenly distributed. New delineations of the regional green belts are currently under discussion for the forthcoming regional plan. The green belts would be substantially enlarged from formerly 281 km² (1966), over 696 km² (2004) to 1103 km² by extending them into the less densely populated outer zones. In the crucial central parts of the Ruhr region, where the original RGBs are located, an ‘adaptive’ reduction will take place as a sacrifice to the already happened change to urban, non-open space land cover. Open spaces will be attached to the original RGBs and form green circles surrounding the cities of the Ruhr region’s core area. We assess the potential ecosystem services provision of the 23 parts of the proposed new regional green belts based on the present land cover. We criticize the planning category regional green belt as indistinct and inappropriate to express the requirements of optimal protection of areas providing ecosystem services. Regional green belts need to be better backed-up by overarching legally binding planning of built-up areas and open space.